PENGAWASAN ADMINISTRATIF TATA USAHA KAYU DI TPK DAN LOGPOND HPH DENGAN PROGRAM KOMPUTER - Hariyatno Dwiprabowo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Ministry of forestry requires the forest concession holders to fill in logs administrative forms containing log records to supervise logs production and circulation in forest concessions. However, large amount of logs produced has prevented the provincial forest service and forest district from conducting through examination on the documents turned in by concessionaries.In this study, a computer program intended to help accomplishing the task is created and tried out documents that must be filled in at logyard and logpond of concession. Using simulated logs data the program run on PC could find some deviation in the documents presented in terms of logs statistics.